Kontribusi Kepemimpinan Pelayan, Etos Kerja, Disiplin Kerja, Kelengkapan Sarana dan Prasarana Terhadap Kinerja Guru - N.K.S. Yuliani; A.A.G. Agung; I.G.K.A. Sunu (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to 1) determine the contribution of servant leadership to teacher performance at SMK Negeri 1 Sawan, 2) determine the contribution of work ethic to teacher performance at SMK Negeri 1 Sawan, 3) determine the contribution of work discipline to teacher performance at SMK Negeri 1 Sawan, 4) knowing the magnitude of the contribution of completeness of facilities and infrastructure to teacher performance at SMK Negeri 1 Sawan, and 5) knowing the magnitude of the simultaneous significant contribution between servant leadership, work ethic, work discipline, completeness of facilities and infrastructure on teacher performance at SMK Negeri 1 Sawan. This type of research is ex-post facto. The population in this study was 53 people. The research sample of this research was 46 people. Collecting data using a Likert scale model questionnaire. Methods of data analysis using descriptive statistical analysis techniques and inferential statistical analysis of multiple regression analysis. The results of the study showed that (1) the contribution of the principal's servant leadership to teacher performance was 19.20%, (2) the contribution of the work ethic to teacher performance was 20.01%, (3) the contribution of work discipline to teacher performance was 17,08%, (4) the contribution of the completeness of facilities and infrastructure to teacher performance is 34,34%, and (5) the contribution of servant leadership style, work ethic, work discipline, completeness of facilities and infrastructure to teacher performance with a contribution of 90.63%.